2006
DOI: 10.1016/j.watres.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of swine wastewater using chlorine, ultraviolet light and ozone

Abstract: Swine wastewater Chlorine Ultraviolet light Ozone A B S T R A C TVeterinary antibiotics are widely used at concentrated animal feeding operations (CAFOs) to prevent disease and promote growth of livestock. However, the majority of antibiotics are excreted from animals in urine, feces, and manure. Consequently, the lagoons used to store these wastes can act as reservoirs of antibiotics and antibiotic-resistant bacteria.There is currently no regulation or control of these systems to prevent the spread of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 24 publications
5
75
2
7
Order By: Relevance
“…Recognizing the potential risk, several research groups have investigated reduction of manure by tertiary treatments that have been used in municipal wastewater treatments. Macauley et al (Macauley et al, 2006) examined the effect of chlorine, ultraviolet light and ozone on swine lagoon bacteria. They found that these treatments at enough concentration or strengths dramatically decreased total bacteria present in swine lagoons, and a combination of chlorine and tetracycline killed all bacteria.…”
Section: Lagoonsmentioning
confidence: 99%
“…Recognizing the potential risk, several research groups have investigated reduction of manure by tertiary treatments that have been used in municipal wastewater treatments. Macauley et al (Macauley et al, 2006) examined the effect of chlorine, ultraviolet light and ozone on swine lagoon bacteria. They found that these treatments at enough concentration or strengths dramatically decreased total bacteria present in swine lagoons, and a combination of chlorine and tetracycline killed all bacteria.…”
Section: Lagoonsmentioning
confidence: 99%
“…Studies have also used UV/O 3 to treat a wide variety of wastewater contaminants including cyanide, swine wastes, quinoline, and landfill leachate (Ford et al, 2006;Macauley et al, 2006;Wang et al, 2004;Wu et al, 2004). UV/O 3 has also been used to remediate NACs.…”
Section: Ultraviolet Light With Ozonementioning
confidence: 99%
“…Among them, Salmonella enterica serovar Typhimurium deserves special attention since it is the most prevalent antimicrobial resistant serovar in swines, and also frequently related to human infections and outbreaks [1]. Several physicochemical approaches are described to control the proliferation of pathogens, such as exposure to UV irradiation [2,3] use of strong oxidant radicals [2], pH increase [4], and selective membranes [5]. However, most if not all of these approaches are not economically feasible.…”
Section: Introductionmentioning
confidence: 99%